KONTRIBUSI KONSEP DIRI SISWA DAN KETERLIBATAN ORANGTUA TERHADAP PEMILIHAN SEKOLAH LANJUTAN - Aswidi Wijaya Cipta; Ratna Wulandari (Program Studi Bimbingan dan Konseling FKIP UMSU, 2018)
Each year students will look for a suitable school before graduation. Problems arise when there are a lot of options that provide diverse schools offer to prospective students. Contributions of students self concept and parents involvement supposed to influence in the selection of secondary schools. This study aimed to describe:1) self-concept students of SMPN 4 Palopo, 2) parents involvement of SMPN 4 Palopo, 3) students secondary school selection, 4) the contribution students self-concept against secondary school selection, 5) contribution parental involvement against secondary school selection, 6) the contribution of students self-concept and parental involvement against secondary school selection. This corelational descriptive research applied quantitative method. The population of the research were students grade IX of SMPN 4 Palopo also using proportional random sampling technique. The instrument of this research was the Likert scale model. The data obtained were analyzed using descriptive statistic, simple regression and multiple regression. The research findings were: 1) students self concept in average were in high category, 2) parental involvement in average were in high category, 3) students selection of secondary school were in high category, 4) there are significance different between students self concept against students selection of secondary school amount 44.3%, 5) there are significance different between parental involvement toward students selection of secondary school amount 51.1%, and 6) there are significance different between students self concept and parental involvement toward students selection of secondary school amount 54.2%. The implication of this research may useful to design career guidance programs.